Non-use of Digital Health Consultations Among Swedish Elderly Living in the Countryside - Landgren, Sara; Cajander, Åsa (Frontiers in Public Health, 2021)
Digital health consultations in primary care have the advantage of offering equal healthcare for people residing in the countryside. While it is gaining acceptance among young- and middle-aged people, the elderly are reluctant to use it. The aim of this study was hence to identify reasons for non-use among elderly in the countryside and describe perceived possible challenges and opportunities with digital health consultations. Semi-structured interviews were conducted with 13 persons over 65 years old residing in the Swedish countryside. There was a mistrust for services offered by private companies and their public funding, a lack of knowledge of available services, and a lack of perceived usefulness. Personal interaction and continuity was more important than time or travel conveniences, although these advantages were recognized. To prevent digital exclusion, caregivers need to offer information, encouragement, or tools for the elderly. Digital primary care also needs to offer familiarity, with continuity and personal connections.